Digital Technology in Politics: To What Extent Indonesian Political Parties Use Social Media to Maintain Existence and Relevance - Dimas Subekti (Universitas Warmadewa, 2025)
This research aims to explain the extent to which Indonesian political parties use social media to maintain their existence and relevance in the political arena. This study uses a qualitative method with a case study approach. The case studies are the Indonesian Democratic Party of Struggle (PDIP), the Golkar Party, and the Gerindra Party. The findings of this study explain that political parties in Indonesia today must carry out organizational transformation to remain relevant and exist in the present and future. This has begun to be done by political parties that utilize digital technology facilities, namely social media by creating accounts and posting professionally packaged content to attract the attention of netizens. PDIP, Golkar, and Gerindra, the top three parties in Indonesia, have actively utilized Instagram and TikTok social media for their party branding needs and to face the 2024 elections by promoting their candidates. In the context of the 2024 Presidential Election, the three political parties are dominant in creating content on Instagram and TikTok regarding the presidential and vice presidential candidates being promoted rather than the political parties themselves. This is an effort by political parties to utilize social media to garner more individual popularity, which leads to the interest in electoral contestation. Political parties that manage their social media professionally are directly proportional to their electoral presence in the community.